Effect of an in-situ thermal annealing on the structural properties of self-assembled GaSb/GaAs quantum dots - Fernández-Delgado, Natalia; Collado, Miriam Herrera; Chisholm, Matthew F.; Ahmad Kamarudin, Mazliana; Zhuang, Qian Dong; Hayne, Manus; Molina, Sergio I. (Elsevier, 2017)
In this work, the effect of the application of a thermal annealing on the structural properties of GaSb/GaAs quantum dots (QDs)1 is analyzed by aberration corrected high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM)2 and electron energy loss spectroscopy (EELS)3 Our results show that the GaSb/GaAs QDs are more elongated after the annealing, and that the interfaces are less abrupt due to the Sb diffusion. We have also found a strong reduction in the misfit dislocation density with the annealing. The analysis by EELS of a threading dislocation has shown that the dislocation core is rich in Sb. In addition, the region of the GaAs substrate delimited by the threading dislocation is shown to be Sb-rich as well. An enhanced diffusion of Sb due to a mechanism assisted by the dislocation movement is discussed.